A Note on the UEK Method - Anna Pajor (Barometr Regionalny, 2018)
The paper concerns certain pitfalls of using the Moore-Penrose pseudoinverse for estimating regression coefficients in linear regression models when the matrix of explanatory variables has not full column rank. The aim of the paper is to show that in this case estimator of parameters based on the Moore-Penrose pseudoinverse is biased, and the bias leads to biased forecasts.